Teacher–Parent Collaboration in Addressing Smartphone Dependency among Madrasah Ibtidaiyah Students: Academic and Socio-Emotional Implications - Mohammad Rofiq; A. Umar; Muhammad Dimas Ardini; Muhammad Habib Husen; Nasikhin Nasikhin; Ahmad Ta'rifin (Yayasan Darussalam Bengkulu, 2026)
This study aims to analyze how the synergy between teachers and parents in ‎instilling digital media discipline helps prevent smartphone addiction among ‎elementary school students in Semarang. The study employs a qualitative ‎approach using a case study design, in which data were collected through in-‎depth interviews with teachers and parents, as well as observations of ‎classroom learning activities. The results indicate that smartphone ‎dependency significantly impacts students' academic, social, and emotional ‎development, characterized by reduced focus on learning, weak self-control, ‎and diminished social interaction and empathy. To address this, three primary ‎forms of synergy between teachers and parents emerged: intensive ‎communication, the establishment of shared rules, and alternative ‎educational activities. Continuous communication fosters shared perceptions ‎and strategies for managing children's device usage. Meanwhile, consistent ‎rules at school and home, as well as engagement in positive activities, have ‎proven effective in fostering students' digital discipline. Theoretically, the ‎findings of this study align with Albert Bandura's Social Cognitive Theory, ‎particularly the concepts of self-regulation and reciprocal determinism, which ‎explain that children's behavior is influenced by the interaction between ‎individual, environmental, and behavioral factors. This suggests that a shift ‎from passive supervision toward active collaboration is necessary to make ‎smartphones a purposeful and valuable learning tool. The contribution of this ‎study lies in the development of a practical collaboration model between ‎teachers and parents based on digital literacy to prevent smartphone ‎dependency among students starting from elementary school age‎.